Adiponectin Paradox in Alzheimer's Disease; Relevance to Amyloidogenic Evolvability? - Waragai, Masaaki; Ho, Gilbert; Takamatsu, Yoshiki; Wada, Ryoko; Sugama, Shuei; Takenouchi, Takato; Masliah, Eliezer; Hashimoto, Makoto (Frontiers in Endocrinology, 2020)
Adiponectin (APN) is a multi-functional adipokine which sensitizes the insulin signals, stimulates mitochondria biogenesis, and suppresses inflammation. By virtue of these beneficial properties, APN may protect against metabolic syndrome, including obesity and type II diabetes mellitus. Since these diseases are associated with hypoadiponectinemia, it is suggested that loss of function of APN might be involved. In contrast, despite beneficial properties for cardiovascular cells, APN is detrimental in circulatory diseases, including chronic heart failure (CHF) and chronic kidney disease (CKD). Notably, such an APN paradox might also be applicable to neurodegeneration. Although APN is neuroprotective in various experimental systems, APN was shown to be associated with the severity of amyloid accumulation and cognitive decline in a recent prospective cohort study in elderly. Furthermore, Alzheimer's disease (AD) was associated with hyperadiponectinemia in many studies. Moreover, APN was sequestered by phospho-tau into the neurofibrillary tangle in the postmortem AD brains. These results collectively indicate that APN might increase the risk of AD. In this context, the objective of the present study is to elucidate the mechanism of the APN paradox in AD. Hypothetically, APN might be involved in the stimulation of the amyloidogenic evolvability in reproductive stage, which may later manifest as AD by the antagonistic pleiotropy mechanism during aging. Given the accumulating evidence that AD and CHF are mechanistically overlapped, it is further proposed that the APN paradox of AD might be converged with those of other diseases, such as CHF and CKD.